2022
DOI: 10.15407/spqeo25.04.385
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion of phosphorus in technology for manufacturing silicon p-i-n photodiodes

Abstract: Comparative characterization of phosphorus diffusion from planar sources and liquid-phase diffusion by using PCl3 in technology for manufacturing silicon p-i-n photodiodes was carried out. The quantitative analysis of dislocations formed when using different variants and modes of diffusion has been performed. The influence of dislocation number on the dark current density and responsivity of photodetectors has been studied. A table has been given for estimation of surface resistance with account of colour inhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…2, 3). In [11] and [13], we found that the optimal values of the surface resistance of phosphorus and boron are R S = 2.7 Ω/□ and R S = 18 Ω/□, respectively. We present the calculations of the charge collection coefficient at these values.…”
Section: Calculationsmentioning
confidence: 93%
See 1 more Smart Citation
“…2, 3). In [11] and [13], we found that the optimal values of the surface resistance of phosphorus and boron are R S = 2.7 Ω/□ and R S = 18 Ω/□, respectively. We present the calculations of the charge collection coefficient at these values.…”
Section: Calculationsmentioning
confidence: 93%
“…The samples were made by diffusion-planar technology according to the technological regimes given in [11]. The thickness of the crystals reached X ≈ 500-510 μm.…”
Section: Methodsmentioning
confidence: 99%
“…It was decided to investigate the influence of the isolation methods of REs based on silicon four-element p-i-n PDs with a guard ring. Production was carried out using diffusion-planar technology according to the technological modes of diffusion processes given in [15]. The starting material was single-crystal dislocation-free p-type silicon with orientation [111], ρ≈17-20 kΩ•cm.…”
Section: Methodsmentioning
confidence: 99%
“…The PD-E technological route consisted of a complex of two thermal operations and three photolithographies: one-stage diffusion of phosphorus in an oxidizing medium was carried out according to the regimes given in [9], during which an n + -layer was formed on both sides of the substrate covered with a SiO 2 film (Fig. 2-b1); further, after chemical dynamic polishing (CDP) of the reverse side of substrate, boron diffusion in the same side to create a p + -type ohmic contact (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The difference in responsivity can be explained by the difference in the life time of minor charge carriers, since responsivity is directly proportional to τ (Eq. ( 1)) [9]. Although the PDs were made of the same silicon, but in the case of PD-E, the degree of degradation of τ during the manufacturing process is smaller due to the reduction in the number of thermal operations…”
Section: Methodsmentioning
confidence: 99%